2015
DOI: 10.1007/s10995-015-1691-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Physical Activity Patterns Across the Lifecourse Impact Birth Outcomes?

Abstract: The significant impact of physical activity during, or immediately prior to pregnancy on a range of pregnancy and birth outcomes has been established. However, lifecourse theory posits that the antecedents of poor outcomes occur across a larger trajectory of time. The objective of this study was to examine whether physical activity patterns over the lifecourse impact birth outcomes. The sample (n = 1,713) was derived from Waves I, III, and IV of the National Longitudinal Study of Adolescent Health and limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…However, we did not identify a pattern of consistently high LTPA, as reported previously (16, 32). We also identified an additional LTSB trajectory with consistently moderate LTSB.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…However, we did not identify a pattern of consistently high LTPA, as reported previously (16, 32). We also identified an additional LTSB trajectory with consistently moderate LTSB.…”
Section: Discussionsupporting
confidence: 47%
“…A previous study of patterns of maternal preconception LTPA and pregnancy outcomes using Add Health data by Vamos et al found that maintaining high LTPA (≥5 times per week, based on meeting physical activity recommendations through 30 minutes of physical activity 5 days per week) in adolescence and adulthood was not associated with low birthweight (OR=0.79; 95% CI: 0.45, 1.39) (16). Vamos et al identified patterns of LTPA a priori, which may not capture observed patterns in the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even among the studies that reported inverse associations there was considerable variability in the strength of the associations reported, with some studies reporting a 15-20% reduction in risk with high physical activity, 35,36,38,42 while other studies reported up to a 40-80% reduction in risk. 19,[32][33][34]41,46,55,56,59 It is possible that differences in the timing, amount, type and intensity of physical activity or different degrees of adjustments for confounders or other study characteristics could explain some of this variation in the results. To clarify whether physical activity before or during pregnancy is associated with the risk of preterm birth, we conducted a systematic review and metaanalysis of epidemiological studies on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…2014 y Vamos y cols. (27)(28)(29)(30)(31)(32). En todos ellos se asegura que el ejercicio físico de intensidad moderada, y efectuado bajo supervisión, desde el primer trimestre y hasta el final del embarazo no afecta al flujo sanguíneo fetoplacentario, y no existen riesgos de parto prematuro ni evidencia científica de daño como resultado de dicha actividad física.…”
Section: Discussionunclassified